RETRACTED: LINC00337 Regulates KLF5 and Maintains Stem-Cell Like Traits of Cervical Cancer Cells by Modulating miR-145 - Han, Qi; Wu, Wenjin; Cui, Yulan (Frontiers in Oncology, 2020)
Accumulating literature and evidence has highlighted the cancer stem-like cell (CSC) model as a cellular mechanism responsible for the phenotypic heterogeneity observed in various types of cancers, including cervical cancer. Long non-coding RNAs (lncRNAs) have been implicated in the retention of stem cell-like traits in cancer cells. However, the role of lncRNAs in the acquisition and maintenance of CSCs in cervical cancer remains largely unknown. Hence, the current study identified that LINC00337 knockdown diminished the CSC-like properties of CD44+/CD24low/-SFCs, evidenced by a decline in the generation of tumorospheres and colonies, a reduction in multi-drug resistance gene-1 (MDR-1), Nanog, Sox2 and Oct4 expression, along with an enhancement in cell apoptosis. RNA pull-down assays and RNA immunoprecipitation revealed the role of LINC00337 as a competing endogenous RNA (ceRNA) of microRNA-145 (miR-145). Furthermore, the miR-145 mRNA target, Kruppel-like factor 5 (KLF5), was decreased in CD44+/CD24low/-SFCs upon LINC00337 knockdown. The in vitro results were reproduced in in vivo studies, which provided verification attesting that LINC00337 knockdown attenuated the tumorigenicity of CD44+/CD24low/-SFCs in nude mice. Taken together, the key findings of the current study demonstrate that LINC00337 acts as an oncogenic lncRNA in cervical cancer and exerts its influence on the expression of KLF5 and the maintenance of cancer stem cell-like properties by means of downregulating miR-145.